Factor analysis and body dimensions of the Japanese quail (Coturnix Coturnix Japonica) (2023)
Morphometric variation can be effectively measured within and between populations and used as a basis for characterization of different livestock types. The study was aimed at contributing to the characterization process of the Japanese quail (mottled brown and white) through quantitative assessment. Zoometrical data on body weight and 11 body measurement were taken on 747 mottled brown quail and 272 white quail from six different farms around Ibadan in the Southwest Nigeria. Descriptive statistics showed that average body weight of Japanese quail reared in Southwest Nigeria were 158.72±2.03, 157.24±1.31, 140.6 ±1.39, and 136.27±2.7g for mottled brown female, brown male, white female and white male, respectively. Sexual dimorphism was observed in all the traits with higher values recorded for the females. Significant correlation (P<0.001) was observed between body weight and body measurements. The best correlation was obtained between body weight and thigh length r = 0.76 and 0.70 for mottled brown quail and white respectively. Factor solution from the principal component analysis, with varimax rotation of the transformation matrix showed three factors were identified in each of the genetic group (total variance of first principal component = 27.86, 30.16, 31.88 and 38.85 for mottled brown male, mottled female, white male, white female quail, respectively). In the two strains of Japanese quail, PC1 had the largest share of the total variance and correlated highly with body weight, breast length, wing length, thigh length and shank length. The PC1 could be used to describe the generalised form of quail. PC2 was orthogonal to PC1 and loaded heavily on breast girth and neck length. Data was also subjected to linear and stepwise regression. More reliable prediction was obtained from stepwise regression, R² was highest with breast girth R²=0.71 and breast length R²=0.81 for brown and white quail, respectively. The weight of Japanese quail is linearly related to body measurements. The high, positive correlation between body weight and zoometric body measurements indicates that these easily measured parts can be used as criteria for assessment and selection of body weight.